Respostas
respondido por:
1
MÉTODO DE SUBSTITUIÇÃO:
{4x + y = 7
{2x - 5y = 9
y = 7 - 4x 2x - 5y = 9
y = 7 - 4.2 2x - 5(7 - 4x) = 9
y = 7 - 8 2x - 35 + 20x = 9
[y = -1] 2x + 20x = 9 + 35
22x = 44
x = 44/22
[x = 2]
Espero ter ajudado. :)
{4x + y = 7
{2x - 5y = 9
y = 7 - 4x 2x - 5y = 9
y = 7 - 4.2 2x - 5(7 - 4x) = 9
y = 7 - 8 2x - 35 + 20x = 9
[y = -1] 2x + 20x = 9 + 35
22x = 44
x = 44/22
[x = 2]
Espero ter ajudado. :)
applequeen:
muchas gracias
respondido por:
0
4x+y=7(5)
2x-5y=9
20x+5y=35
2x-5y=9
22X = 44 ==> x = 2
y = 7 - 4x ==. y = 7 -4(2) ==. y = 7 - 8 ==. y = - 1
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás